THE INFLUENCE OF AUDIT COMMITTEE, MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP AND PROPORTION OF INDEPENDENT BOARD OF COMMISSIONERS ON EARNINGS MANAGEMENT (In Manufacturing Companies Of The Consumption Goods Industry Sector Listed In Indonesia Stock Exchange 2013 - 2017 Periods) - Pambudi, Januar Eky; Siregar, Indra Gunawan; Annisa, Dea (Dynamic Management Journal, 2020)
This study aims to analyze the factors that influence earnings management. The factors analyzed in this study were the audit committee, managerial ownership, institutional ownership, and the proportion of independent board of directors as independent variables while earnings management was the dependent variable.The population of this study is a manufacturing company in the consumer goods industry listed on the IDX for the 2013-2017 periods. While the research sample was determined by purposive sampling method to obtain 7 sample of the company. The data used is obtained from the company's financial statements published on the official website www.idx.co.id. The analytical method used is the Data Panel Regression at a significance level of 5% and with the help of software Eviews 9.0.The results showed that the audit committee had a significant negative effect on earnings management, managerial ownership had no significant effect on earnings management, institutional ownership had no significant effect on earnings management, the proportion of independent board had a significant positive effect on earnings management. But the audit committee, managerial ownership, institutional ownership, and the proportion of independent board of directors have a significant effect on earnings management. Keywords: Earnings Management, Audit Committee, Managerial Ownership, Institutional Ownership, and Proportion of Independent Commissioners.